Neuronal oscillations and speech perception: critical-band temporal envelopes are the essence - Ghitza, Oded; Giraud, Anne-Lise; Poeppel, David (Frontiers in Human Neuroscience, 2013)
A recent opinion article (Neural oscillations in speech: don’t be enslaved by the envelope. Obleser et al., 2012) questions the validity of a class of speech perception models inspired by the possible role of neuronal oscillations in decoding speech (e.g., Ghitza 2011, Giraud & Poeppel 2012). They criticize, in particular, what they see as the over-emphasis of the role of temporal speech envelope information, and the over-emphasis of entrainment to the input rhythm while neglecting the role of top-down processes in modulating the entrainment of neuronal oscillations. Here we respond to these arguments, referring to the phenomenological model of Ghitza (2011), taken as a representative of the criticized approach.